2013
DOI: 10.4161/pri.23807
|View full text |Cite
|
Sign up to set email alerts
|

Beta conformation of polyglutamine track revealed by a crystal structure of Huntingtin N-terminal region with insertion of three histidine residues

Abstract: Huntington disease is an autosomal-dominant neurodegenerative disorder caused by a polyglutamine (polyQ) expansion (> 35Q) in the first exon (EX1) of huntingtin protein (Htt). mHtt protein is thought to adopt one or more toxic conformation(s) that are involved in pathogenic interactions in cells . However, the structure of mHtt is not known. Here, we present a near atomic resolution structure of mHtt36Q-EX1. To facilitate crystallization, three histidine residues (3H) were introduced within the Htt36Q stretch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 57 publications
2
54
0
Order By: Relevance
“…To better characterize this conformational heterogeneity, we applied an integrative structure determination approach based on all information available for the Rvb1/Rvb2/Ino80INS complex including the XL-MS dataset (Figures 3C, Table S4), the consensus cryo-EM map (Figure 5B), the comparative model of the Rvb1/Rvb2 dodecamer, the crystal structure of MBP (Kim, 2013), and the predicted secondary structure of Ino80INS (Figure S6, Table S6). The resulting integrative models are expected to be more accurate and precise than models based on a subset of data (Alber et al, 2007; Robinson et al, 2015; Russel et al, 2012; Shi et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…To better characterize this conformational heterogeneity, we applied an integrative structure determination approach based on all information available for the Rvb1/Rvb2/Ino80INS complex including the XL-MS dataset (Figures 3C, Table S4), the consensus cryo-EM map (Figure 5B), the comparative model of the Rvb1/Rvb2 dodecamer, the crystal structure of MBP (Kim, 2013), and the predicted secondary structure of Ino80INS (Figure S6, Table S6). The resulting integrative models are expected to be more accurate and precise than models based on a subset of data (Alber et al, 2007; Robinson et al, 2015; Russel et al, 2012; Shi et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Novel oligomers of htt exon1 have also been identified in an in vitro mammalian system (45). Furthermore, distinct, polymorphic aggregates of htt have been observed (48), and x-ray crystallography has demonstrated that monomeric htt adopts multiple conformations (49, 50). These studies point to the complex nature of polyQ aggregation, necessitating the use of techniques capable of extracting quantitative data concerning relative amounts of specific aggregates forms.…”
Section: The Complexity Of Polyq-mediated Aggregation In Httmentioning
confidence: 99%
“…The cross-beta structure was confirmed by solid state-NMR on exactly the same D2Q15K2 peptides (Schneider et al 2011) and both cross-beta and the characteristic steric zipper of the side chains in poly-Q amyloid fibers have been shown by simulations (Man, Roland & Sagui 2015). Other studies have shown that the structures of the poly-Q segments, which depend on the length of the repeat track, temperature and other experiment parameters (Vitalis, Wang & Pappu 2008; Deng, Wang & Ou-Yang 2012; Buchanan et al 2014), can exist in α-helical configuration (Kim, Chelliah, Kim, Otwinowski & Bezprozvanny 2009), loop (Kim et al 2009), β-hairpin (Kim 2013) and β-sheet (Miettinen, Knecht, Monticelli & Ignatova 2012; Buchanan et al 2014). …”
Section: Introductionmentioning
confidence: 99%